2012
DOI: 10.1007/s00586-012-2435-4
|View full text |Cite
|
Sign up to set email alerts
|

The use of antibiotic-impregnated fibrin sealant for the prevention of surgical site infection associated with spinal instrumentation

Abstract: Purpose The purpose of this study was to determine if the use of antibiotic-impregnated fibrin sealant (AFS) was effective in preventing surgical site infections (SSI) associated with spinal instrumentation. Methods In a preliminary study, five pieces of vancomycin-impregnated fibrin sealant, five nuts that were not treated with the sealant, and five nuts that were treated with the sealant were subjected to agar diffusion testing. In a clinical study, the rates of deep SSI were compared between 188 patients wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 23 publications
0
26
0
Order By: Relevance
“…aureus contaminated rat model of titanium spine clip implantation [292]. The second paper found similar results suggesting a benefit to combining vancomycin with fibrin sealant on in-vitro agar plates [293]. The investigators also performed a sequential clinical study comparing surgically placed orthopedic hardware without ( n = 188, 2003–2007) and with ( n = 196, 2007–2010) local application of the antibiotic impregnated fibrin sealant and found significant reductions in the rates of surgical site infection in the antibiotic fibrin sealant hardware group (0/196, 0% versus 11/188, 5.8%, P = 0.0003) [293].…”
Section: Less Frequently Published Clinical Applications Of Fibrinmentioning
confidence: 92%
“…aureus contaminated rat model of titanium spine clip implantation [292]. The second paper found similar results suggesting a benefit to combining vancomycin with fibrin sealant on in-vitro agar plates [293]. The investigators also performed a sequential clinical study comparing surgically placed orthopedic hardware without ( n = 188, 2003–2007) and with ( n = 196, 2007–2010) local application of the antibiotic impregnated fibrin sealant and found significant reductions in the rates of surgical site infection in the antibiotic fibrin sealant hardware group (0/196, 0% versus 11/188, 5.8%, P = 0.0003) [293].…”
Section: Less Frequently Published Clinical Applications Of Fibrinmentioning
confidence: 92%
“…Considering the natural presence of fibrin in the healing process, fibrin is employed by surgeons as a sealant for general wound hemostasis. Fibrin sealants have also been utilized for infection prophylaxis by adding powdered antibiotic to the polymerizing fibrin gel at the site of wound closure [131]. …”
Section: Experimental Biomaterials For Local Antibiotic Deliverymentioning
confidence: 99%
“…Tofuku et al reported that the use of an antibiotic-impregnated fibrin sealant (AFS) significantly reduced the rates of deep surgical site infections (SSIs) in patients who underwent implantation of orthopedic hardware surgery; 11 of the 188 patients acquired a deep SSI in the group treated without AFS while none of the 196 patients acquired a deep SSI in the other group. 181 Another research area is the treatment of bone defects that suffer from infection. Co-delivery of antibiotic and osteogenic cells via a fibrin scaffold may be an ideal option.…”
mentioning
confidence: 99%